Formulasi Media Produksi Bibit F2 Jamur Tiram Putih - Ika Oksi Susilawati; Witiyasti Imaningsih; Arif Mulyanto (Biology Department, Faculty of Science and Technology, Univeristas Jambi, Indonesia, 2017)
White oyster mushroom (Pleurotus ostreatus L.) is a fungus that consumption demand by people Banjarbaru. However, the fulfillment of this fungus is still lacking, has always supplied from Java. Based on these problems, it is necessary to study the composition of the growth media F2 seeds oyster mushroom. The purpose of this study was to determine the composition ratio of constituents of seedling growth media appropriate for the growth of white oyster mushroom seeds. This research was conducted by dividing some compositions media. Comparison of composition constituents of the right media is used to make seedling growth media F2 is a mixture of sawdust with grain (50%: 50%). In addition the use of pure sawdust can also be used as a media for the manufacture of white oyster mushroom F2 seeds. The composition of the media mix sawdust with grain (50%: 50%) effectively used to create F2 seed oyster mushroom.